Pension Policy and Governmentality in China: Manufacturing Public Compliance - Yan Wang (LSE Press, 2022)
Rapid economic growth is often disruptive - so how has the Chinese state been able to maintain compliance from its people while pursuing an exceptionally fast social and economic transformation? This crucial question is explored through detailed analysis of the trajectories, policy rationale, and effects of China's pension reforms, demonstrating how statecraft shapes the ways in which citizens ascribe credit and responsibility for pensions protection to themselves, the state, and other actors. In Pension Policy and Governmentality in China, Yan Wang shows that China's governmentality for manufacturing compliance is hybrid, organic, and dynamic. Targeted allocation of benefits, policy experimentation, propaganda, and knowledge construction are all used to shape public expectations and to justify state rule. An original contribution to the study of legitimation in modern states, this book demonstrates how, when active counter-conduct is concerned, individuals may choose cognitive rebellion and falsify their public compliance.
Keywords: 300; Statecraft; Social Security; China; Pensions